2017
DOI: 10.1016/j.jiph.2017.01.023
|View full text |Cite
|
Sign up to set email alerts
|

Are the Saudi parents aware of antibiotic role in upper respiratory tract infections in children?

Abstract: Upper respiratory tract infection (URTI) is considered to be the most common reason for children's visits to emergency departments or outpatient clinics. The misuse and overuse of antibiotics are currently major public health problems worldwide. This study aimed to assess Saudi parents' knowledge, attitude, and practice (KAP) regarding the use of antibiotics in URTIs in children. This cross-sectional study was conducted in Saudi Arabia using a previously validated questionnaire, which was distributed using Twi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
38
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(45 citation statements)
references
References 21 publications
4
38
1
Order By: Relevance
“…Most of respondents have recently used antibiotics as well as the majority used them for viral diseases and for cold and cough. These results are similar to other studies conducted in KSA that showed a wrong practice among the Saudi subjects as most of them would use antibiotics without prescriptions, they used antibiotics for cough and cold (12,13) .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Most of respondents have recently used antibiotics as well as the majority used them for viral diseases and for cold and cough. These results are similar to other studies conducted in KSA that showed a wrong practice among the Saudi subjects as most of them would use antibiotics without prescriptions, they used antibiotics for cough and cold (12,13) .…”
Section: Discussionsupporting
confidence: 90%
“…The majority of respondents had inadequate knowledge regarding the use of antibiotics without prescriptions. In consistence, a same pattern of antibiotic use without prescriptions was found in KSA (12)(13)(14) .…”
Section: Discussionsupporting
confidence: 60%
“…Misunderstanding the role of antibiotics in treating viral diseases can influence patient’s opinion. Conversely, lack of knowledge regarding optimal treatment of children diagnosed with URIs has been shown to lead to incorrect attitude in parents, despite specific education . A study conducted in the Netherlands reported that approximately half of the respondents believed that antibiotics are effective for treatment of viral infections .…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, lack of knowledge regarding optimal treatment of children diagnosed with URIs has been shown to lead to incorrect attitude in parents, despite specific education. 73 A study conducted in the Netherlands reported that approximately half of the respondents believed that antibiotics are effective for treatment of viral infections. 49 Another study in Poland showed that inappropriate belief of effective antibiotic therapy for RTIs has led to self-medication in patients.…”
Section: Discussionmentioning
confidence: 99%
“…URTI can be caused by viruses, such as Adenovirus and Rhinovirus 6 . URTI included in most frequent infection diseases in children with six to eight episodes in a year and it's categorized into the most frequent reason for children to go to emergency room 7 .…”
Section: Introductionmentioning
confidence: 99%